Vibration-Induced-Emission (VIE) for imaging amyloid β fibrils. (29th November 2016) - Dou, Wei-Tao; Chen, Wei; He, Xiao-Peng; Su, Jianhua; Tian, He
Abstract : This paper discusses the use of N, N ′-disubstituted-dihydrodibenzo[ a, c ]phenazines with typical Vibration-Induced-Emission (VIE) properties for imaging amyloid β (Aβ) fibrils, which are a signature of neurological disorders such as Alzheimer's disease. A water-soluble VIEgen with a red fluorescence emission shows a pronounced, blue-shifted emission with Aβ peptide monomers and fibrils. The enhancement in blue fluorescence can be ascribed to the restriction of the molecular vibration by selectively binding to Aβ. We determine an increasing blue-to-red emission ratio of the VIEgen with both the concentration and fibrogenesis time of Aβ, thereby enabling a ratiometric detection of Aβ in its different morphological forms. Importantly, the VIEgen was proven to be suitable for the fluorescence imaging of small Aβ plaques in the hippocampus of a transgenic mouse brain (five months old), with the blue and red emissions well overlapped on the Aβ. This research offers a new rationale to design molecular VIE probes for biological applications.